2023
DOI: 10.1161/strokeaha.123.041783
|View full text |Cite
|
Sign up to set email alerts
|

BAG3 Overexpression Attenuates Ischemic Stroke Injury by Activating Autophagy and Inhibiting Apoptosis

Abstract: Background: The ubiquitin-proteasome system (UPS) and autophagy are 2 major protein degradation pathways in eukaryotic cells. We previously identified a switch from UPS to autophagy with changes in BAG3 (B-cell lymphoma 2-associated-athanogene 3) expression after cerebral ischemia in mice. BAG3 is an antiapoptotic-cochaperone that is directly involved in cellular protein quality control as a mediator for selective macroautophagy. Here, we aimed to investigate the role of BAG3 in ischemic stroke. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…The predicted core genes are critical to the pathogenesis+ADs- hSPA5, for example, offering neuroprotection in ischemic strokes[ 34 ]. BAG3 overexpression is shown to improve neurological outcomes associated with middle cerebral artery embolism in mice, reducing infarct volume and enhancing cell survival by activating autophagy and inhibiting apoptosis[ 35 ]. Ischemia-induced neuronal autophagy is shown to exacerbate microglial inflammation post-stroke, possibly due to the reduced CX3CL1 expression in autophagic neurons[ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The predicted core genes are critical to the pathogenesis+ADs- hSPA5, for example, offering neuroprotection in ischemic strokes[ 34 ]. BAG3 overexpression is shown to improve neurological outcomes associated with middle cerebral artery embolism in mice, reducing infarct volume and enhancing cell survival by activating autophagy and inhibiting apoptosis[ 35 ]. Ischemia-induced neuronal autophagy is shown to exacerbate microglial inflammation post-stroke, possibly due to the reduced CX3CL1 expression in autophagic neurons[ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…NO, as a potent vasodilator, can improve blood flow, reduce vascular inflammation, and inhibit apoptosis ( Chen et al, 2023 ). Apoptosis is one of the key factors leading to neuronal death in patients with IS ( Liu et al, 2023 ). Thus, activating the VEGFA/eNOS pathway can weaken apoptosis and improve neurological recovery after cerebral ischemia ( Liu et al, 2020b ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, in mice undergoing MCAO, autophagy inhibition with 3-Methyladenine (3-MA) was shown to exacerbate brain injury. Mechanistically, overexpression of BAG3 (B-cell lymphoma 2-associated-athanogene 3), a protein involved in cellular protein quality control, activates autophagy and prevents both apoptosis and cerebral injury ( Liu et al, 2023 ). Another study demonstrated that CAPN1 (calpain1), an intracellular Ca 2+ -regulated cysteine protease, is activated in the cortex of rats undergoing permanent MCAO.…”
Section: Protective Effect Of Autophagy In Animal Models Of Ismentioning
confidence: 99%